Tests on the efficiency of the power plant at the Kansas State Agricultural College - Fockele, Glick; Cole, Murray S. (My University, 1902)
Introduction: The plant is designed to furnish heat and power for the various departments at the Kansas State Agricultural College of Manhattan, Kansas. It was originally intended by the writers to include in their work, tests on the heating power of the plant, but the arrangement of their other college work during the year, made it impossible for them to conduct the experiments at a time when the heating plant was in operation. Another drawback was the absence of suitable apparatus for the determination of the calorific power of the coal. The heating plant consists of six externally fired, horizontal, multitubular boilers, designated as No. 1, 2, 3, 4, 5 and 6. Five are of 60 nominal horsepower and one, No. 6, is of 100 nominal horsepower. The tests were conducted upon No. 1, for the reason that it was the only high pressure boiler which was piped for individual feed water, and with this boiler is our interest concerned. None of the connections with other boilers could possibly affect results of these tests except in the test on April 28th, when No. 3 was turned in on account of the heavy load on the engine. In this case neither boiler made more steam than the engine could use, so the pressure in neither one was affected in the least and the conditions of the test were kept uniform. The boiler itself is 54” diameter, with 34 flues 3-3/4 inches in diameter and 16 feet long. The grates are 4-1/2’ by 4-1/2’. The boiler was built by Joseph Bromich of Topeka, Kansas. It was installed in 1896. It was in very good condition for all tests. The fuel used was the coal furnished by the state for use in the institution, and was of very poor quality. It comes from the state mines near Leavenworth, and is mined by the prisoners from the state penitentiary.
Citation: Fockele, Glick and Cole, Murray S. Tests on the efficiency of the power plant at the Kansas State Agricultural College. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Kansas State Agricultural College; Power Plant; Testing; Efficiency; Theses